Cherry Fruit Fly, Rhagoletis cingulata (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems (EDIS)
The cherry fruit fly (adult) or cherry maggot (larva) attacks cherry and causes wormy fruits. In Florida, it attacks wild cherries and is of little economic importance. Across its range, it breeds in all varieties of cherries including the sweet cherry. This revised 3-page fact sheet was written by H. V. Weems Jr., and published by the UF Department of Entomology and Nematology, January 2012.